Multilayer adsorption of Cu(II) and Cd(II) over Brazilian Orchid Tree (Pata-de-vaca) and its adsorptive properties - Jorgetto, Alexandre de Oliveira [UNESP]; Silva, Adrielli Cristina Peres da [UNESP]; Wondracek, Marcos Henrique Pereira [UNESP]; Silva, Rafael Innocenti Vieira da [UNESP]; Velini, Edivaldo Domingues [UNESP]; Saeki, Margarida Juri [UNESP]; Pedrosa, Valber de Albuquerque [UNESP]; Castro, Gustavo Rocha de [UNESP] (Elsevier B.V., 2015)
Through very simple and inexpensive processes, pata-de-vaca leaves were turned into a powder and applied as an adsorbent for the uptake of Cu(II) and Cd(II) from water. The material was characterized through SEM, EDX, FTIR and surface area measurement. The material had its point of zero charge determined (5.24), and its adsorption capacity was evaluated as a function of time, pH and metal concentration. The material presented fast adsorption kinetics, reaching adsorption equilibrium in less than 5 min and it had a good correlation with the pseudo-second order kinetic model. Optimum pH for the adsorption of Cu(II) and Cd(II) were found to be in the range from 4 to 5, approximately. In the experiment as a function of the analyte concentration, analogously to gas adsorption, the material presented a type II isotherm, indicating the formation of multilayers for both species. Such behavior was explained with basis in the alternation between cations and anions over the material's surface, and the maximum adsorption capacity, considering the formation of the multilayers were found to be 0.238 mmol L-1 for Cu(II) and 0.113 mmol L-1 for Cd(II).
Keywords: Adsorption; Solid-phase extraction; Heavy metal; Decontamination; Wastewater treatment; Separation technique